2022
DOI: 10.1111/ppl.13643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated air temperature coupling with soil drought on carbohydrate metabolism and oil synthesis during cottonseed development

Abstract: Cotton, as the fifth-largest oilseed crop, often faces the coupling stress of heat and drought. Still, the effects of combined stress on cottonseed oil synthesis and its closely related carbon metabolism are poorly investigated. To this end, experiments were conducted with two cultivars (Sumian 15 and PHY370WR) under two temperature regimes: ambient temperature (AT) and elevated temperature (ET, which was 2.5 C-2.7 C higher than AT) and three water regimes: optimum soil moisture (soil relative water content [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Different soil-moisture treatments began at the early stage of flowering. When the soil moisture reached the predetermined level, the temperature treatments were established (Figure S1) according to our previous report [10], using a Temperature Control System (OTC, Southeast Co., Ltd., Ningbo, China) to raise the ambient temperature 2-3 • C. The mean daily temperatures in the ambient and the elevated temperature areas in 2019 and 2020 are shown in Table S1. The mean daily temperature in the ambient temperature area in 2019 and 2020 were 31.7 • C and 31.2 • C, respectively, lower than the upper limit of 32 • C of the optimum temperature range for cotton development [37].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Different soil-moisture treatments began at the early stage of flowering. When the soil moisture reached the predetermined level, the temperature treatments were established (Figure S1) according to our previous report [10], using a Temperature Control System (OTC, Southeast Co., Ltd., Ningbo, China) to raise the ambient temperature 2-3 • C. The mean daily temperatures in the ambient and the elevated temperature areas in 2019 and 2020 are shown in Table S1. The mean daily temperature in the ambient temperature area in 2019 and 2020 were 31.7 • C and 31.2 • C, respectively, lower than the upper limit of 32 • C of the optimum temperature range for cotton development [37].…”
Section: Experimental Designmentioning
confidence: 99%
“…Drought is also the main abiotic stress factor that limits crop growth, especially drought occurring at the flowering and boll-forming stage, leading to a significant decrease in pollen fertility, which is not conducive to fertilization and fruiting [6], therefore reducing the crop yield [7,8]. Moreover, heat and drought stresses usually occur simultaneously under field conditions, and some studies have explored the effects of combined stress of drought and heat temperature on the physiological and metabolic activities in cotton (Gossypium hirsutum L.) leaves, fibers, and seeds [9,10]. However, there are few studies on the effects of the combined stress of drought and high temperature on the physiological and metabolic activities of cotton male organs and their relationship with pollen fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, investigations into sucrose and starch metabolism have revealed that high-temperature treatment can increase the sucrose content in plants [ 14 ]. Under conditions of drought or high-temperature drought, both sucrose and starch contents decrease significantly, indicating that drought activates plant's ability to degrade sucrose [ 15 ]. The influence of high temperature and drought on plant starch remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from pre-harvest insect stresses, oilseeds are also susceptible to post-harvest heat stresses, particularly during the processing stage ( Oliete, Lubbers, Fournier, Jeandroz, & Saurel, 2022 ; Xu et al, 2022 ; D. Zhu, Guan, Fan, Sun, & Wang, 2022 ). The functional health components of oilseeds are also often destroyed by these insect/heat stresses, which lessens the oilseeds' health benefits and economic value ( Memoli et al, 2017 ; Valencic, Butinar, Podgornik, & Bucar-Miklavcic, 2021 ).…”
Section: Introductionmentioning
confidence: 99%